Homeostasis and transitional activation of regulatory T cells require c-Myc - Saravia, Jordy (Sci Adv, 2020)
Regulatory T cell (T(reg)) activation and expansion occur during neonatal life and inflammation to establish immunosuppression, yet the mechanisms governing these events are incompletely understood. We report that the transcriptional regulator c-Myc (Myc) controls immune homeostasis through regulation of T(reg) accumulation and functional activation. Myc activity is enriched in T(regs) generated during neonatal life and responding to inflammation. Myc-deficient T(regs) show defects in accumulation and ability to transition to an activated state. Consequently, loss of Myc in T(regs) results in an early-onset autoimmune disorder accompanied by uncontrolled effector CD4(+) and CD8(+) T cell responses. Mechanistically, Myc regulates mitochondrial oxidative metabolism but is dispensable for fatty acid oxidation (FAO). Indeed, T(reg)-specific deletion of Cox10, which promotes oxidative phosphorylation, but not Cpt1a, the rate-limiting enzyme for FAO, results in impaired T(reg) function and maturation. Thus, Myc coordinates T(reg) accumulation, transitional activation, and metabolic programming to orchestrate immune homeostasis.